+0  
 
0
36
1
avatar

Let f(x) = 7x + 5 and g(x) = x + 1. If h(x) = f(g(x)) , then what is the inverse of h(x)?

 Apr 7, 2022
 #1
avatar+23183 
0

f(x)  =  7x + 5                 g(x)  =  x + 1

 

f (g(x) )  =  f( x + 1 )  =  7(x + 1) + 5  =  7x + 7 + 5  =  7x + 12

 

h(x)  =  7x + 12

 

Substituting  'y'  for  'h(x)'        [making it easier to write]

     y  =  7x + 12

 

Finding the inverse:

     x  =  7y + 12     --->     x - 12  =  7y     --->     y  =  (x - 12) / 7

 

f-1(x)  =  (x - 12) / 7

 Apr 7, 2022

7 Online Users